2013
DOI: 10.1080/11250003.2013.861024
|View full text |Cite
|
Sign up to set email alerts
|

Effects of photoperiod on egg production inEurytemora affinisPoppe, 1880 (Copepoda: Calanoida) from the Seine Estuary (France)

Abstract: The calanoid copepod Eurytemora affinis Poppe, 1880 is the most abundant species of the mesozooplanktonic community of the Seine estuary (France) in the lower salinity zone. Diapausing eggs of this species have been found in the sediment of this estuary but they are few in comparison with those found for other calanoid species. We thus decided to test the effect of photoperiod on diapausing egg production in E. affinis from the Seine estuary. For this, an experimental device has been developed. A combination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…These two factors are the most characteristic factors that change seasonally. Many copepod species, have been shown to increase the production of resting eggs as a function of temperature and/or photoperiod (Arndt and Schnese, 1986;Dahms, 1995;Chinnery and Williams, 2003;Drillet et al, 2006;Holste and Peck, 2006;Wu et al, 2006;Hansen et al, 2010;Yoshida et al, 2012;Berasategui et al, 2013;Glippa et al, 2013;Peck et al, 2015). However, other abiotic and biotic factors also elicit the production of resting eggs, such as food availability (Drillet et al, 2011), abrupt salinity changes (Højgaard et al, 2008) and crowding (Ban and Minoda, 1994).…”
mentioning
confidence: 99%
“…These two factors are the most characteristic factors that change seasonally. Many copepod species, have been shown to increase the production of resting eggs as a function of temperature and/or photoperiod (Arndt and Schnese, 1986;Dahms, 1995;Chinnery and Williams, 2003;Drillet et al, 2006;Holste and Peck, 2006;Wu et al, 2006;Hansen et al, 2010;Yoshida et al, 2012;Berasategui et al, 2013;Glippa et al, 2013;Peck et al, 2015). However, other abiotic and biotic factors also elicit the production of resting eggs, such as food availability (Drillet et al, 2011), abrupt salinity changes (Højgaard et al, 2008) and crowding (Ban and Minoda, 1994).…”
mentioning
confidence: 99%
“…() revealed that copepod dormant eggs production is highly variable among individuals and populations. In addition, a diversity of diapausing eggs production has been well demonstrated in different populations of widely distributed calanoid copepods Eurytemora affinis and A. tonsa (Ban, ; Drillet, Goetze, Jepsen, Højgaard & Hansen, ; Drillet, Jepsen, Højgaard, Jørgensen & Hansen, ; Glippa, Alekseev & Souissi, ), and it is considered as a function of genetic differentiation or micro‐evolutionary divergence due to geographic isolation (Drillet, Jepsen, et al., ; Glippa et al., ). For aquaculture applications, the quiescent eggs are much feasible as resources of live prey for fish larvae, because the nauplii hatch faster from quiescent eggs than from diapausing eggs.…”
Section: Discussionmentioning
confidence: 99%
“…hatched normally in complete darkness, whereas eggs from Acartia clausi were adversely A COPEPOD EGG IS NOT JUST AN EGG affected by darkness. The production of diapausing eggs in the key species, Euthynnus affinis, within the downstream Seine estuary could be induced by short days, but photoperiod was probably not the only driver responsible for the induction of diapausing egg production (Glippa et al, 2013).…”
Section: Lightmentioning
confidence: 99%
“…Many marine copepod species have been shown to increase production as a function of photoperiod and/or temperature (e.g., Sullivan and McManus, 1986;Dahms, 1995;Chinnery and Williams, 2003;Peck and Holste, 2006;Wu et al, 2006;Yoshida et al, 2012;Glippa et al, 2013;Peck et al, 2015). However, multiple other abiotic and biotic factors potentially influencing the production of resting eggs have been identified for copepods in general, but the number of actual factors identified to induce the production of resting eggs in marine copepods is not vast or fully understood (see Dahms, 1995;Fig.…”
Section: Cues Promoting Production Of Resting Eggsmentioning
confidence: 99%